Comparison of PET/MRI With PET/CT in the Evaluation of Disease Status in Lymphoma. (January 2017) - Afaq, Asim; Fraioli, Francesco; Sidhu, Harbir; Wan, Simon; Punwani, Shonit; Chen, Shih-hsin; Akin, Oguz; Linch, David; Ardeshna, Kirit; Lambert, Jonathan; Miles, Kenneth; Groves, Ashley; et al.
Abstract : Purpose: The primary aim was to compare the diagnostic performance of PET/MRI (performed with basic anatomical MRI sequences) in detecting sites of disease in adult patients with lymphoma compared with the current standard of care, PET/CT. Secondary aims were to assess the additional value of diffusion-weighted imaging to PET/MRI in disease detection and to evaluate the relationship between the standardized uptake value on PET/MR and the apparent diffusion coefficient on diffusion-weighted imaging. Methods: Sixty-eight studies in 66 consecutive patients with histologically proven Hodgkin or non-Hodgkin lymphoma were prospectively evaluated. Each patient had whole body PET/CT, followed by whole body PET/MR. Two experienced readers independently evaluated the PET/MRI studies, and two other experienced readers independently evaluated PET/CT. Site of lymphoma involvement and SUVmax at all nodal sites more avid than background liver were recorded. Readers provided stage (in baseline cases) and disease status (remission vs active disease). The apparent diffusion coefficient mean value corresponding to the most avid PET site of disease was recorded. Results: Ninety-five nodal and 8 extranodal sites were identified on both PET/CT and PET/MRI. In addition, 3 nodal and 1 extranodal sites were identified on PET/MRI. For positive lesion detection, reader agreement in PET/MR was perfect between the 2 readers and almost perfect between PET/CT and PET/MR (k > 0.978). Intermodality agreement between PET/CT and PET/MRI was also near perfect to perfect for staging/disease status k = (0.979–1.000). SUVmax from PET/CT and PET/MRI correlated significantly (Spearman rho correlation coefficient, 0.842; P < 0.001). Diffusion-weighted imaging did not alter lesion detection or staging in any case. A negative correlation was demonstrated between ADC mean and SUVmax (Spearman rho correlation coefficient r, −0.642; P < 0.001). Conclusions: PET/MRI is a reliable alternative to PET/CT in the evaluation of patients with lymphoma. Diffusion-weighted imaging did not alter diagnostic accuracy. With comparable accuracy in detection of disease sites and added benefit of radiation dose reduction, PET/MRI has a potential to become part of routine lymphoma imaging.